Studies on genetic variability, inheritance and heterosis in pepper (Capsicum annuum L.) - Fite, Geleta Legesse (University of the Free State, 2003)
The knowledge of genetic similarity and dissimilarity among crop cultivars is of vital importance for the plant breeder. The genetic variability of 39 pepper (Capsicum annuum L.) genotypes of different varietal groups that were obtained from different geographical origins was studied using morphological traits and amplified fragment length polymorph isms (AFLP) markers. Both methods showed moderately high genetic distances among the different genotypes indicating genetic diversity among the total genotypes. However, when a comparison was made between the Ethiopian and the exotic genotypes, the mean genetic distance among Ethiopian genotypes was lower than that between the Ethiopian and the exotic ones. The dendrogram based on morphological data clustered the genotypes on the basis of fruit size and was generally consistent with different varietal groups. Similarly, with AFLP data, genotypes with similar fruit sizes clustered together. Combining ability and heterosis estimates are important to determine the direction and goals of a breeding program. Seven diverse parental lines were selected from the 39 genotypes and crossed in a half-diallel method. The parental lines and their 21 FI hybrids were evaluated to estimate the combining abilities and genetic effects determining the heritability of various characters, and to determine heterosis of hybrids over mid-parent, high-parent and standard checks for various characters. Generally, significant general (GCA) and specific (SCA) combining abilities were observed for all measured characters indicating the presence of both additive and non-additive gene actions. However, additive gene action is more important than non-additive gene action, as the magnitude of GCA effects was much higher than SCA effects. The estimates of predictability ratios for fruit length, fruit diameter, fruit weight, pericarp thickness and fruit number were closer to unity, suggesting the possibility of predicting progeny performance based on parental GCA alone. High heritability both in broad and narrow senses was also recorded for these characters indicating their inheritance is less influenced by the environment. Substantial heterosis over mid-parent, high-parent and the standard check was observed. Many crosses demonstrated high heterosis for fruit yield, fruit diameter, mean fruit weight and pericarp thickness over the standard check. For the traits of earliness (days to flowering, days to maturity and fruit maturation period), the overall mean mid-parent, high-parent and standard heterosis were negative. Thus, it can be suggested that with the proper choice of parents, pepper hybrids that have higher yield potential, good fruit characteristics and early maturity can be developed to increase pepper productivity in Ethiopia. Genetic diversity between parents may contribute positively to both heterosis and trangressive segregation. The relationship between genetic diversity of the seven parental lines, and heterosis and hybrid performance was assessed. The genetic diversity was measured using 15 morphological traits and six AFLP primer combinations. Cluster analysis using the two genetic distance measures generally grouped the seven parents differently. Morphological distance was negatively correlated only with mid-parent heterosis (MPH) for days to flowering and days to maturity. The correlations of AFLP measured genetic distances with mid-parent and high-parent heterosis were non significant for all characters with the exception of fruit diameter and proved to be of no predictive value. In addition to single crosses, three-way and double crosses can be used to overcome the low productivity of inbred lines. It is hypothesized that yield stability is high in three-way and double-cross hybrids owing to higher genetic heterogeneity as compared to single cross hybrids. Twenty-six genotypes, including six inbred lines, eight single, six threeway and six double crosses were evaluated for yield and other agronomic characters in two environments using a randomized complete block design with three replications. The three categories of hybrids performed differently across the environments and showed high variations for the majority of characters studied. Three-way crosses gave the highest mean fruit yield per plant followed by double crosses. The two types of hybrids were also more stable than the single crosses. In general, three-way crosses showed promising performance for the studied traits. The highest estimates of mid- and high-parent heterosis were also observed in the three-way and double cross hybrids. Therefore, the low productivity of local pepper cultivars in Ethiopia can be overcome through developing and utilizing three-way and double cross hybrids.

Die kennis van genetiese ooreenkomste en verskille tussen cultivars is van kritiese belang vir die planteteler. Die genetiese variabiliteit van 39 rissie (Capsicum annuum L.) genotipes van verskillende groepe en geografiese oorspronge is bestudeer met die gebruik van morfologiese eienskappe en AFLP (amplified fragment length polymorphism) merkers. Beide metodes het redelike hoë genetiese afstande getoon tussen genotipes, wat die teenwoordigheid van genetiese diversiteit tussen genotipes aantoon. Toe 'n vergelyking getref is tussen Etiopiese en eksotiese genotipes, was die gemiddelde genetiese afstand tussen Etiopiese genotipes laer as tussen Etiopiese en eksotiese cultivars. Die dendrogram wat gebasseer is op morfologiese data, het die genotipes gegroepeer op die basis van vrug grootte en dit was oor die algemeen in ooreenstemming met die verskillende produksie groepe. Net so, met AFLP data het genotipes met dieselfde vrug grootte saam gegroepeer. Kombineervermoë en heterose bepalings is belangrik om die rigting en die doelstellings van 'n teelprogram te bepaal. Sewe diverse ouer lyne is geselekteer van die 39 genotipes en is gekruis in 'n half-dialleel. Die ouer lyne en hulle 21 Fl basters is geëvalueer om kombineervermoë en genetiese effekte te bereken wat oorerflikheid bepaal van verskillende eienskappe, en om heterose van basters oor die mid-ouer, hoogste ouer en standaarde vir verskillende eienskappe vas te stel. Oor die algemeen was daar betekenisvolle algemene- (OCA) en spesifieke (SCA) kombineervermoë vir alle gemete eienskappe, wat die aanwesigheid van beide additiewe en nie-additiewe geen aksie aantoon. Additiewe geen aksie was egter meer belangrik as nie-additiewe geen aksie, omdat die grootte van OCA effekte baie hoër was as die SCA effekte. Die berekening van voorspelbaarheids verhoudings van vrug lengte, vrug deursnee, vrug gewig, perikarp dikte en aantal vrugte was nabyeen, wat aangedui het dat die nageslag se eienskappe voorspel kan word vanaf die ouerlike OCA. Hoë oorerflikhede in die breë en nou sin was ook teenwoordig vir hierdie eienskappe wat aangetoon het dat oorerflikheid nie baie deur die omgewing beïnvloed is nie. 'n Hoë vlak van heterose oor die mid-ouer en standaarde is uitgedruk. Heelwat kruisings het hoë vlakke van heterose getoon vir vrug opbrengs, vrug deursnee, gemiddelde vrug gewig en perikarp dikte teenoor die standaard. Vir vroegheids eienskappe( dae tot blom, dae tot rypheid en vrug rypheids tyd) was die algehele mid-ouer, hoogste ouer en standaard heterose negatief. Daar kan dus gesê word dat met 'n goeie keuse van ouers, rissie basters met 'n groter opbrengs potensiaal, goeie vrug eienskappe en vroeë rypheid ontwikkel kan word om rissie produktiwiteit in Etiopië te verhoog. Genetiese diversiteit tussen ouers kan positief bydra tot beide heterose en transgressiewe segregasie. Die verhouding tussen genetiese diversiteit van die sewe ouer lyne en heterose en baster prestasie is geassesseer. Die genetiese diversiteit is gemeet deur die gebruik van 15 morfologiese eienskappe en ses AFLP kombinasies. Groeperings analise wat twee genetiese afstands metings metodes gebruik, het die sewe ouers verskillend gegroepeer. Morfologiese afstand was negatief gekorreleer net met mid-ouer heterose vir dae tot blom en dae tot rypheid. Die korrelasie van AFLP gemete genetiese afstande met mid-ouer en hoogste ouer heterose was nie betekenisvol nie vir alle eienskappe behalwe vrug deursnee, en was van geen voorspellende waarde nie. Buiten enkel kruisings, kan drierigting en dubbel kruisings gebruik word om lae produktiwiteit van ingeteelde lyne te oorkom. Daar is 'n hipotese dat opbrengs stabiliteit hoog is in drierigting- en dubbel kruis basters a.g.v. hoër genetiese heterogeniteit in vergelyking met enkelkruis basters. Ses en twintig genotipes, insluitend ses ingeteelde lyne, agt enkel, ses drierigting en ses dubbel krusings is geëvalueer vir opbrengs en ander agronomiese eienskappe in twee omgewings met 'n gerandomiseerde blokontwerp met drie herhalings. Die drie kategorië van basters het verskillend gereageer oor omgewings en het groot variasie getoon vir die meeste eienskappe wat gemeet is. Drierigting kruisings het die meeste vrugte per plant gelewer, gevolg deur dubbel kruisings. Die twee tipes basters was ook meer stabiel as die enkel kruisings. In die algemeen het drierigting kruisings belowende potensiaal getoon vir gemete eienskappe. Die hoogste bepalings van mid-ouer en hoogste ouer heterose is gesien vir drierigting en dubbel kruis basters. Daarom kan die lae produktiwiteit van plaaslike rissie cultivars in Etiopië oorkom word deur die ontwikkeling en gebruik van drierigting en dubbel kruis basters.
Thesis (Ph.D. (Plant Sciences, Plant Breeding))--University of the Free State, 2003
Keywords: Capsicum annuum -- Genetics; Peppers -- Breeding -- South Africa; Heterosis